Pengaruh Pendapatan dan Jumlah Tanggugan Keluarga Serta Tingkat Pendidikan Terhadap Konsumsi Penduduk di Kecamatan Samarinda Ilir - Musjadir Musjadir B; Muhammad Saleh; Nurjanana Nurjanana (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This research aims to know the effects of income, the amount of family dependents, and the degree of education towards resident’s consumption at Samarinda Ilir Sub-district. This research is a quantitative research. Data of this research were collected using the prime data and the analyses tools of double linear regression of SPSS application version 23. The result of this research shows that variable of income gives significance effects towards residents’ consumption at Samarinda Ilir Sub-district. The amount of family dependents gives significance effects towards residents’ consumption at Samarinda Ilir Sub-district, and the degree of education gives significance effects towards residents’ consumption at Samarinda Ilir Sub-district.